Analysis and more General Solutions of Einstein Field Equation in f(R, T) Gravity - Alhefthi, Reem K.; Iqbal, Muhammad Sajid; Sohail, Saba; İnç, Mustafa (Springer/Plenum Publishers, 2024)
In this paper the major work is done on the optimal solution of f(R, T) gravity 00-component field equation. Explicit derivation of 00 and 11-components has been done. Optimal existence of solution of 00-component has been formulated using fixed point theory. The equivalence of 00-component of f(R, T) gravity field equation with wave equation having the source term has been explicitly proved. Also the computational more general solutions of 00-component of f(R, T) gravity field equation is explained in the various surface plot. Also the contour as well as 2D-pairs (f, R) and (f, T) have been examined and analyzed.
Keywords: General relativity; Einstein field equation; Wave equivalence; Simulation of f(R; T) gravity theory